MODEL OF PUBLIC RELATIONS MANAGEMENT DEVELOPMENT WITH ISLAMIC EDUCATIONAL INSTITUTIONS ACCORDING TO THE MERDEKA LEARNING PERSPECTIVES - Untung, Slamet; Rohayana, Ade Dedi; Farid, M. Miftah (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This study attempts to analyze the model developed by public relations with Islamic educational institutions as the former Pekalongan Residency according to the perspective of Merdeka Learning by making Madrasah Aliyah as the object of research. This study is intended to find a model of public relations management with Islamic educational institutions at the MA level in the Merdeka Learning perspective that was developed, the strategies used in the development model of public relations management with Isla mic educational institutions in the Merdeka Learning perspective at the MA level, and the impact of the community relations development model on madrasas. The location of this research is Madrasah Aliyah, the former Pekalongan Residency, Central Java. The primary data of this research is a model of public relations development with Islamic educational institutions in Madrasah Aliyah. At the same time, the secondary data is the theoretical basis obtained through a literature review. This research is qualitative research with the type of field research. In comparison, the data collection techniques used interviews, observation, and documentation (triangulation) equipped with audio and visual. The data were analyzed using the descriptive-analytic method. The results showed that the model of developing public relations management with Islamic educational institutions at the MA level was two-way symmetrical, two-way asymmetrical, and general information. While the strategy used is more based on the use of media. One of the impacts of the public relations management development model is the increase in the quality of the madrasa.